Management and resource sharing of trade and business information; development of a regional database of trade publications - Allsopp, Judith (CEDP St. MichaelBD, 1992)
Highlights the role and function of Documentaton Centres. Reviews some of the issues which impact on resource sharing and the development of a regional database of trade publications. Identifies the components of successful database development.